Transformasi Media Massa Menuju Era Masyarakat Informasi di Indonesia - Respati, Wira (Humaniora, 2014)
Indonesia is now on the transition toward the Age of Information Society. In this period, the pattern of gathering as well as distributing information change. This situation is in accordance with the change of human lifestyle as the concequences of Information Communication Technology (ICT) adoption. Their tools in communicating offer more opportunies and interactive characteristics. Moreover, the use of social media applications, which one of them is blog based on web 2.0, opens possibilities for the audience to give more active roles in gathering and distributing news, just like what professional journalists do. The question now is about how the practioners of mainstream news face this phenomenon, what they should do to maintain their existence in media industry. They should not ignore the growth of virtual community as well as citizen journalism. They cannot also pretend that there is no change on their audience behavior in consuming media. On the contrary, they do need to give space to their audiences who are in transtition toward the age of information society, to participate creatively in gathering and producing information.